ANALISA PERENCANAAN STRUKTUR ATAS PADA APARTEMEN GRAND JATI JUNCTION MEDAN DI ZONA A - Rahelina Ginting; Nelson Hutahaean; Ferry Tampubolon (JURNAL ILMIAH TEKNIK SIPIL, 2021)
A planner is required to be able to design with high usability, efficiency, and aesthetics. Many aspects must be considered when designing a construction, one of which is concrete. The effect of earthquake loads is one of the important things to analyze because the effects on buildings can be harmful to humans. Therefore, a good design is needed in order to reduce the level of accidents and losses caused. In this thesis, the building being reviewed is a 30-floor apartment building which is the newest apartment in the city of Medan. The calculation of the structure refers to SNI 2847-2013 for reinforced concrete designs, SNI 1726-2012 for designs against earthquakes and SNI 1727-2013 for loading on structures. The calculation of the building structure is reviewed for dead loads, live loads and earthquake loads. Calculations carried out include slab, beam, column and foundation elements. The SAP 2000 application was used to help calculate the structural element forces. From the calculation results there were differences with the designs used in the field, this happened because each structural planner used certain calculation rules and procedures in designing the structure. However, the difference between the results of the analysis and the design in the field is not very significant, so we can assume that the beam, column and floor slab designs are safe to use.